Pengelolaan Malaleuca cajuputi Sebagai Sumber pendapatan masyarakat di Wasur Kampung Provinsi Papua Selatan - Dharma Gyta Sari Harahap; Ferry Irawan; Muh. Rafi'y; Siti Meutia Sari (Jurnal Transformasi Pendidikan Indonesia, 2024)
The community service is motivated by the importance of improving the economy of the community in Wasur Village to help the community in meeting the economic elements of the community in Wasur Village. The community service is carried out through a direct mentoring process to the community so that the community service is able to help the community apply the principles of green economy by utilizing local potential, namely the distribution of eucalyptus oil in Wasur Village which can be managed directly by the community. Through direct mentoring, it will effectively help improve the economic level of the community in Wasur Village.